Identification of potential biomarkers for breast cancer based on salivary metabolomics - Jiang, Xinyu; Jia, Yumei; Zhang, Bo; Yang, Kai; Li, Yang (Frontiers in Oncology, 2025)
IntroductionBreast cancer (BC) remains the most prevalent malignant tumor in women worldwide and a leading cause of cancer-related mortality. Early screening is essential to improve prognosis, yet current diagnostic methods are often invasive or lack sensitivity. Saliva is an accessible and non-invasive biofluid containing various metabolites that reflect systemic physiological and pathological changes. Thus, salivary metabolomics may provide novel insights into breast cancer-associated metabolic alterations and support the development of early diagnostic strategies.ObjectivesTo explore the salivary metabolomic profile of breast cancer patients and identify potential non-invasive biomarkers for early breast cancer screening.MethodsSaliva samples were collected from a screening set consisting of 30 BC patients and 20 normal controls (NC) volunteers. untargeted metabolomics approach was performed using liquid chromatography–tandem mass spectrometry (LC-MS/MS). Principal component analysis (PCA) and orthogonal partial least squares-discriminant analysis (OPLS-DA), along with KEGG pathway enrichment and receiver operating characteristic (ROC) curve analyses, were employed to characterize metabolic differences and identify potential biomarkers. Additionally, saliva samples from a validation set (52 BC patients and 52 NC volunteers) were collected. Enzyme-linked immunosorbent assay (ELISA) was used to quantify potential biomarkers, and their diagnostic performance was evaluated through ROC curve analysis.ResultsA total of 101 differential metabolites were identified, including 81 upregulated and 20 downregulated compounds. Screening identified 2-aminonicotinic acid and theobromine as potential diagnostic biomarkers. Analysis of the validation set demonstrated that 2-aminonicotinic acid (AUC: 0.81, cut-off: 5.88 ng/mL) and theobromine (AUC: 0.75, cut-off: 5.27 ng/mL) exhibit promising diagnostic potential.ConclusionThe salivary metabolome of breast cancer patients displays distinct changes compared to healthy individuals. Salivary 2-aminonicotinic acid and theobromine emerge as promising non-invasive biomarkers for breast cancer detection. Nevertheless, larger-scale validation studies are warranted to substantiate their specificity and clinical utility.